Co-production of "nature walks for wellbeing" public health intervention for people with severe mental illness: use of theory and practical know-how - Gill Hubbard; Catharine Ward Thompson; Robert Locke; Dan Jenkins; Sarah-Anne Munoz; Hugo Van Woerden; Margaret Maxwell; Yaling Yang; Trish Gorely (BMC, 2020)
Abstract Background Interventions need to be developed in a timely and relatively low-cost manner in order to respond to, and quickly address, major public health concerns. We aimed to quickly develop an intervention to support people with severe mental ill-health, that is systematic, well founded both in theory and evidence, without the support of significant funding or resource. In this article we aim to open and elucidate the contents of the 'black box' of intervention development. Methods A multidisciplinary team of seven academics and health practitioners, together with service user input, developed an intervention in 2018 by scoping the literature, face-to-face meetings, email and telephone. Researcher fieldnotes were analysed to describe how the intervention was developed in four iterative steps. Results In step 1 and 2, scoping the literature showed that, a) people with severe mental illness have high mortality risk in part due to high levels of sedentary behaviour and low levels of exercise; b) barriers to being active include mood, stress, body weight, money, lack of programmes and facilities and stigma c) 'nature walks' has potential as an intervention to address the problem. In Step 3, the team agreed what needed to be included in the intervention so it addressed the "five ways to mental wellbeing" i.e., help people to connect, be active, take notice, keep learning and give. The intervention was mapped to key behavioural change concepts such as, personal relevance, relapse prevention, self-efficacy. In Step 4, the team worked out how best to implement the intervention. The intervention would be delivered over 12 weeks by members of the hospital team and community walk volunteers. Participants would receive a nature walks booklet and text messages. Conclusions We developed a theoretically-informed, evidence-based nature walks programme in a timely and relatively low-cost manner relevant in an era of growing mental illness and funding austerity. Further research is required to test if the intervention is effective and if this approach to intervention development works.